2015
DOI: 10.4055/cios.2015.7.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Ceramic Total Hip Arthroplasty in Patients with Cerebral Palsy: Does It Work?

Abstract: BackgroundAdult patients with cerebral palsy (CP), who have advanced degenerative arthritis of the hip, have been treated with resection arthroplasty and arthrodesis. Although total hip arthroplasty (THA) has also been used as one of the alternative options, there are few studies on contemporary bearings used in THA. Therefore, we evaluated the results of the contemporary ceramic-on-ceramic THA in adult patients with CP.MethodsFrom January 2005 to December 2007, five adult CP patients (5 hips) underwent THA us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Many patients undergoing THA have had previous operations, such as a soft-tissue release, osteotomy, excision arthroplasty, open reduction and internal fixation and spinal fusion. The percentage of patients who had undergone previous surgery, when this was reported, was 40%, 10 53%, 6 56%, 5 and 60%. 8 …”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Many patients undergoing THA have had previous operations, such as a soft-tissue release, osteotomy, excision arthroplasty, open reduction and internal fixation and spinal fusion. The percentage of patients who had undergone previous surgery, when this was reported, was 40%, 10 53%, 6 56%, 5 and 60%. 8 …”
Section: Resultsmentioning
confidence: 87%
“…Some authors reported selective use of constrained liners for instabilty, abductor insufficiency or hyperlaxity. 5 , 7 , 17 Yoon et al 10 reported good outcomes when using a ceramic-on-ceramic bearing. A dual mobilityarticulation was used by some authors to increase stability.…”
Section: Resultsmentioning
confidence: 99%
“…At 10 years, the survival rate collected by three studies was of 83.8%. 29 , 31 , 35 Implant preferences are specified in 11 studies, 23 , 25 , 26 , 29 36 and 243 cemented, 231 uncemented, 85 hybrid, and 14 reverse hybrid. Two studies describe the use of hip resurfacing techniques, 25 , 36 and one study describes the use of humeral stem in 12 hips 30 ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The authors found 14 studies regarding neuromuscular hip dysplasia and THA. [23][24][25][26][27][28][29][30][31][32][33][34][35][36] Going from 1993 to 2021, this selection mainly includes retrospective cohort studies.…”
Section: Neuromuscular Hip Dysplasiamentioning
confidence: 99%
“…Among seven other retrospective studies, at varying lengths of follow-up, revision rates ranged from 0% to 27%. These studies with a combined 189 patients at mean 94 months of follow-up, reported 20 dislocations (10.6%), 11 cases of aseptic loosening (5.8%), 6 infections (3.2%), and 6 periprosthetic fractures (3.2%) [ [40] , [41] , [42] , [43] , [44] , [45] , [46] ]. While there was considerable heterogeneity across the studies with regard to severity of CP symptoms, functional improvements were noted in multiple studies, including cases of both mild and severe impairment [ 41 ].…”
Section: Resultsmentioning
confidence: 99%